Analysis Of Determining Legal Status And Distribution Of Inheritance In Polygamous Marriages (Study Decision No. 1491/Pdt.G/2022/Pa Stb) - Muhammad Khairi; Saidin Rosnidar Sembiring (Ilmu Hukum Prima (IHP), 2025)
Stabat Religious Court Case Number 1491/Pdt.G/2022/PA.Stb describes an inheritance conflict involving a husband with two wives (previously divorced from his first wife) and six children. This case demonstrates how the unclear status of joint property, unilateral claims by one party, and the refusal to distribute inheritance according to Islamic law can trigger legal disputes. A crucial point, which gave rise to legal irregularities, was that the trial facts did not find evidence of permission from the religious court for the second marriage performed by the plaintiffs' father in 1982. This is despite the fact that Law No. 1 of 1974 was already in effect at the time, which expressly requires court permission for a second marriage. Strangely, despite the lack of permission from the religious court, the second marriage was still administratively registered by the Tebing Tinggi Religious Affairs Office and resulted in a marriage certificate. This study used a normative juridical method with additional data collection techniques through informant interviews. The results showed an error in considering the legality of a second marriage that lacked court permission. The court declared the second wife as the heir, even though the marriage did not legally meet the requirements for polygamy under the Marriage Law and the Compilation of Islamic Law. This violates the principles of legal certainty, justice, and legal protection for the other parties (the first wife and her children), who have a stronger legal position. This decision demonstrates the need for consistency in the application of legal norms so that legal principles, particularly justice and certainty, can be fully upheld.